When Does Religion Matter With Regard to Crime? Examining the Relationship Between Genetics, Religiosity, and Criminal Behavior - Watts, Stephen J. (Criminal justice and behavior, 2018)
Religiosity has been shown to be a predictor of initial criminal offending, reoffending, and desistance. To date, however, research has generally failed to assess the role that biological factors play in moderating the religiosity-crime relationship. The present study utilizes a nationally representative sample of male adolescents (N = 4,053), to explore whether variants of the dopamine transporter gene (DAT1) and the monoamine oxidase A gene (MAOA) interact with religiosity to affect self-reported criminal offending. Results of negative binomial regressions demonstrate that religiosity interacts with these genes to influence offending among males, net of controls. Importantly, once potential confounding variables are accounted for, a statistically significant effect of religiosity on offending among males is only evident for those who carry plasticity alleles for both DAT1 and MAOA (vs. carrying one or zero plasticity alleles). Thus, among males, whether religiosity is important for criminal offending depends partly on the individual genotype. Implications for theory and policy are discussed.